Der politische Hintergrund zur Errichtung des Unterrichts- und Cultusministeriums 1849 - Gebhard Bendler (Historia.scribere)
The following seminar-paper is about the political background of the incorporation of the Austrian Ministry for Education and Culture in the year 1849. It will examine the impact of the revolution in 1848 on the development of a “modern” Austrian eductional system.